2021
DOI: 10.1016/j.ejca.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 vaccine mimics lymph node metastases in patients undergoing skin cancer follow-up: A monocentre study

Abstract: Introduction The Covid-19 pandemic has changed the lives of people around the world. Fortunately, sufficient vaccines are now available. Local reactions with ipsilateral lymphadenopathy are among the most common side effects. We investigated the impact of lymphadenopathy after Covid-19 vaccination on the value of ultrasound in tumor patients. Patients and methods Patients with melanoma or merkel cell carcinoma were included who underwent lymph node excision and received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“… 53 Furthermore, 18 cases who developed lymphadenopathy following COVID‐19 vaccination conducted different tests such as FDG‐PET‐CT scan, MRI, US, and/or FNA biopsy without having any malignancies. 21 , 22 , 28 , 33 , 34 , 37 , 49 In a recent study, Placke et al, 67 reported 8 patients (with melanoma or Merkel cell carcinoma) who were misdiagnosed with lymph nodes metastases and underwent lymph node excision following COVID‐19 vaccination. 68 Therefore, care must be taken before suspecting lymph node metastasis or deciding for lymphadenectomy following COVID‐19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Furthermore, 18 cases who developed lymphadenopathy following COVID‐19 vaccination conducted different tests such as FDG‐PET‐CT scan, MRI, US, and/or FNA biopsy without having any malignancies. 21 , 22 , 28 , 33 , 34 , 37 , 49 In a recent study, Placke et al, 67 reported 8 patients (with melanoma or Merkel cell carcinoma) who were misdiagnosed with lymph nodes metastases and underwent lymph node excision following COVID‐19 vaccination. 68 Therefore, care must be taken before suspecting lymph node metastasis or deciding for lymphadenectomy following COVID‐19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…KFD very uncommonly occurs following vaccination, with only rare reports in the literature describing its occurrence after influenza vaccination [7], human papillomavirus vaccination and Japanese encephalitis virus vaccination [8]. A literature search yielded only one case report of KFD following COVID-19 vaccination at the time of writing [3], with many other papers describing cytologic or histologic findings of reactive follicular hyperplasia or reactive lymphadenopathy [9][10][11][12][13][14]. Table 1 details the key features of published cases of lymphadenopathy post COVID-19 vaccination, which also had cytologic and/or histologic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date, no studies have examined lymph nodes histologically after COVID-19 mRNA vaccination in such a way that would have allowed conclusions to be drawn; however, Placke et al reported a lymph node dissection due to suspected malignancy in a patient who received a COVID-19 vaccine. Only marked follicular hyperplasia was found [ 31 ]. In this type of reaction, the lymph node follicles enlarge at the expense of other nodal structures and therefore, the lymph node becomes relatively more homogenous.…”
Section: Discussionmentioning
confidence: 99%